Unraveling mechanisms of value co-creation in festivals - Mervi Luonila; Kati Suomi; Tanja Lepistö (Cognizant Communication Corporation, 2022)
The aim of this qualitative case study is to explore the mechanisms underlying value co-creation in the context of networked festival productions. Applying the managerial perspective, this study particularly explores why co-creation represent a valuable factor in networked festival productions and how the activities are conducted in the value creative platform, namely conversational space. Considering festivals as services in their host destinations, this study applies the context of three festivals in one city in Finland and draws on the literature on festival management, service experience, and value co-creation.
The study shows that the co-creation of conversational space fosters value co-creation as an interactive process, that is, as a mechanism of value co-creation. Conversational space is found to intertwine the festival with its host community and therefore influencing to the justification of a festival’s existence by empowered legitimacy. Festival managers need to consider conversational space as strategically crucial because of the need to gain public support for festival and to enhance the justification and existence of festival in its destination.